Hydrocolloid edible coatings extend shelf life, reduce postharvest decay, and maintain keeping quality of mango fruits (Mangifera indica L.) under ambient storage. Issue 12 (13th October 2022) - Prasad, Killi; Sharma, Ram Roshan; Asrey, Ram; Sethi, Shruti; Srivastav, Manish; Singh, Dinesh; Arora, Ajay
Abstract: Mango fruit exhibit high postharvest losses due to physiological, biochemical, and pathological deterioration during storage. Edible coatings such as hydrocolloids (HC) bear promising potential for fruit quality preservation at ambient storage due to its triple action (physiological, biochemical and pathological) on fruit and thus widely researched in recent years. This study demonstrates the influence of health and eco‐safe hydrocolloid edible coatings such as "Carboxymethyl cellulose" (CMC) (1%), "Guar gum" (1.5%), "Gum Arabica" (10%), and "Xanthan gum" (0.3%) as dip treatment to enhance the postharvest quality and storage life of mangoes at ambient storage (25 ± 4°C and 65 ± 5% RH). "Xanthan gum" (0.3%) treatment exhibited the highest efficacy in reducing the decay loss by more than threefold and physiological loss by twofold over control fruit. It lowered the physiological and fruit softening enzyme activities (PG, PME, and LOX), while maintaining the biochemicals. Moreover, it maintained both internal as well as external (consumer preference) quality of fruit and extended 6 days shelf life on the physiological loss standard basis (≤10%) than that of the control. The results recommend the application of "Xanthan gum" (0.3%) as an efficacious ecological, sustainable, and health‐friendly surface edible coating for quality preservation and storage period extension of mango fruit under ambient storage. Practical applications: The selected hydrocolloid edible coatings dip treatment showed promising potential in controlling the physiological, biochemical, and pathological deterioration of mango fruit stored under ambient condition. The selected treatments extended the shelf life without diminishing fruit quality. However, among the attempted HC treatments, the "Xanthan gum" (0.3%) (XG) coating displayed the excellent results. It added the storage life of mango fruit by 6 days over the control. XG treated fruit displayed the excellent results in terms of storage period extension, quality retention, consumer preference, and control over the fruit decay and softening enzymes activities. Postharvest preservation of mango fruit using HC is nonchemical, cost‐effective approach which is GRAS (generally recognized as safe), health, and eco safe. Abstract : Postharvest qulaity preservation and shelf life extension of mango fruit using hydrocollod edible coating.